A method for isolation of cone photoreceptors from adult zebrafish retinae. Issue 1 (December 2016) - Glaviano, Antonino; Smith, Andrew; Blanco, Alfonso; McLoughlin, Sarah; Cederlund, Maria; Heffernan, Theresa; Sapetto-Rebow, Beata; Alvarez, Yolanda; Yin, Jun; Kennedy, Breandán
Abstract Background Cone photoreceptors are specialised sensory retinal neurons responsible for photopic vision, colour perception and visual acuity. Retinal degenerative diseases are a heterogeneous group of eye diseases in which the most severe vision loss typically arises from cone photoreceptor dysfunction or degeneration. Establishing a method to purify cone photoreceptors from retinal tissue can accelerate the identification of key molecular determinants that underlie cone photoreceptor development, survival and function. The work herein describes a new method to purify enhanced green fluorescent protein (EGFP)-labelled cone photoreceptors from adult retina of Tg(3.2gnat2:EGFP ) zebrafish. Results Methods for dissecting adult zebrafish retinae, cell dissociation, cell sorting, RNA isolation and RNA quality control were optimised. The dissociation protocol, carried out with 30 retinae from adult zebrafish, yielded approximately 6 × 106 cells. Flow cytometry cell sorting subsequently distinguished 1 × 106 EGFP+ cells and 4 × 106 EGFP− cells. Electropherograms confirmed downstream isolation of high-quality RNA with RNA integrity number (RIN) >7.6 and RNA concentration >5.7 ng/µl obtained from both populations. Reverse Transcriptase-PCR confirmed that the EGFP-positive cell populations express known genetic markers of cone photoreceptors that were not expressed in the EGFP-negative cell population whereas a rod opsin amplicon was only detected in the EGFP-negative retinal cell population. Conclusions This work describes a valuable adult zebrafish cone photoreceptor isolation methodology enabling future identification of cone photoreceptor-enriched genes, proteins and signalling networks responsible for their development, survival and function. In addition, this advancement facilitates the identification of novel candidate genes for inherited human blindness.